Sistem Pengambilan Dan Pengembalian Rekam Medis Rawat Inap Berbasis Web Menggunakan Metode Prototype Di RSUD Arifin Achmad Provinsi Riau - Sukmawati Ambar Kristianing Putri; Niyalatul Muna; Feby Erawantini; M. Choirur Roziqin (Universitas Duta Bangsa Surakarta, 2021)
The Regional General Hospital of Arifin Achmad, Riau Province, carries out the process of retrieving and returning inpatient medical records is still manual, namely still using the expedition book. By still using the expedition book, the process of searching for medical records of inpatients who will seek treatment will take longer if they have not been returned from the inpatient room. Returns of medical records between Januari 2019-December 2019 experienced a delay of 71,78%. The purpose of this study was tho design and create a system for retrieving and returning inpatient medical records to overcome the problem of inaccurate returns. This type of research is to use the prototype development method. Data collection was carried out through interviews, observation, documentation and Focused Groub Discussion (FDG). System design is done using flowcharts, Context Diagrams, Level 1 Data Flow Diagram, and Entity Relationship Diagrams. Making a system using the programming language PHP and MySQL as the database. Testing of this system is Black Box Testing by testing the software in terms of functional specifications without testing the design and program code. This test is used to determine user or user satisfaction with the software that has been mad. The result of the tests carried out stated that the functionality of the retrieval system for inpatient medical record was running well or was successful. The result of this research is a system that can help the process of retrieving and returning medical records so that it can reduce the number of inaccuracies in returning with a reminder message via telegram if the medical records are not returned immediately.